2004
DOI: 10.1002/cncr.20064
|View full text |Cite
|
Sign up to set email alerts
|

Cervical adenocarcinoma and squamous cell carcinoma incidence trends among white women and black women in the United States for 1976–2000

Abstract: BACKGROUNDAlthough cervical carcinoma incidence and mortality rates have declined in the U.S. greatly since the introduction of the Papanicolaou smear, this decline has not been uniform for all histologic subtypes. Therefore, the authors assessed the differential incidence rates of squamous cell carcinoma (SCC) and adenocarcinoma (AC) of the cervix by race and disease stage for the past 25 years.METHODSData from nine population‐based cancer registries participating in the U.S. Surveillance, Epidemiology, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
270
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(293 citation statements)
references
References 82 publications
15
270
1
7
Order By: Relevance
“…Moreover, the decrease in the incidence of ACIS is mainly caused by ACIS lesions with a concurrent squamous dysplasia. The only two previous studies of AC and ACIS trends, both in the United States, found an increase in the incidence of ACIS without a significant change in AC incidence over a 20-year period (Plaxe and Saltzstein, 1999;Wang et al, 2004). This stable pattern in AC incidence accords with an earlier report from the Netherlands (Bulk et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, the decrease in the incidence of ACIS is mainly caused by ACIS lesions with a concurrent squamous dysplasia. The only two previous studies of AC and ACIS trends, both in the United States, found an increase in the incidence of ACIS without a significant change in AC incidence over a 20-year period (Plaxe and Saltzstein, 1999;Wang et al, 2004). This stable pattern in AC incidence accords with an earlier report from the Netherlands (Bulk et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…We used the same database but extended the analysis to an additional 5 years, making short-term fluctuations in AC incidence less important. This unchanged AC incidence contrasts with the incidence rates reported from other countries where it is rising (Zheng et al, 1996;Vizcaino et al, 1998;Bergstrom et al, 1999;Plaxe and Saltzstein, 1999;Smith et al, 2000;Liu et al, 2001;Sasieni and Adams, 2001;Visioli et al, 2004;Wang et al, 2004;Bray et al, 2005). However, a stable pattern has been reported more often (Vizcaino et al, 1998;Chan et al, 2003;Bulk et al, 2005), although a decreasing incidence has also been recorded (Vizcaino et al, 1998;Bray et al, 2005;Howlett et al, 2007).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Cervical squamous cell carcinoma (CSCC) is the most common pathological type of cervical cancer followed by cervical adenocarcinoma and adenosquamous carcinoma (2). The association between human papillomavirus (HPV) infection and the occurrence of cervical cancer has been verified by numerous studies (3,4).…”
Section: Introductionmentioning
confidence: 99%